A comparison study on the blood transfusion reaction between the elective and the emergency operationâs patients - Ishandono Dachlan, Hidayati Samsiarah (Universitas Gadjah Mada, 2011)
Blood transfusion is principally a process of transferring blood or blood components from one individual (the donor) toanother individual (the recipient). Blood transfusion can be either a life saving condition or a life threatening situation dueto the complications happened. Therefore, blood transfusion should be conducted with clear and accurate indication inorder to obtain a condition in which the advantages outweighs the disadvantages. The aim of this study was to evaluatethe differences of the blood transfusion reactions between the patients underwent the emergency surgery with theelective surgery. This was a cross sectional study using data from the medical records from January to December 2009and from the observation on blood transfusion patients from January to May 2010. Data were analyzed using independentt-test, Chi-square test or the logistic regression, with 95% confidence interval (p<0.05). Two hundred and sixty eightdata from medical records and directly observation on blood transfusion patients were obtained during the study. Thewere significant differences of patient reactions after blood transfusion on both types of operation and blood componentstransferred (p<0.05).The transfusion reactions were more frequent in emergency surgery (54.9%) compared withelective surgery (30.5%). Based on types of blood component transfered, the transfusion reaction was more frequentafter Whole Blood/WB transfusion (84.9%) compared with Packed Red Cell/PRC transfusion (25.1%) and Fresh FrozenPlasma/FFP transfusion (25%). The types of operation and blood products had been proven to be the risk factors in bloodtransfusion. Moreover the blood products contributed more in the transfusion reactions compared with the types ofoperation (p<0.05). Amount of transfused blood based on haemoglobin correction formula on both the emergency orelective operations was not significantly different (p>0.05). In conclusion, blood transfusion reactions happened morefrequently in emergency surgery than elective surgery. The WB also generated transfusion reaction more frequently thanthe PRC. The amount of blood required based on hemoglobin correction formula for most patients was similar to the bloodtransfused.Key words: blood transfusion-type of operation-transfusion reaction - whole blood-haemoboglobin correction formula